Acetylcholinesterase Inhibitory Pyridine Alkaloids of the Leaves of Senna multijuga - Serrano, Maria A. R. [UNESP]; Pivatto, Marcos [UNESP]; Francisco, Welington [UNESP]; Danuello, Amanda [UNESP]; Regasini, Luis O. [UNESP]; Lopes, Elaine M. C.; Lopes, Márcia Nasser [UNESP]; Young, Maria C. M.; Bolzani, Vanderlan da Silva [UNESP] (Amer Chemical Soc, 2010)
Two unusual pyridine alkaloids, 7'-multijuguinone (1) and 12'-hydroxy-7'-multijuguinone none (2), were isolated front the leaves of Senna multijuga, together with the known flavonoid rutin. The structures of the new alkaloids were established oil the basis of spectroscopy data interpretation. Compounds I and 2 exhibited moderate in vitro acetylcholinesterase (AChE) inhibitory activity, in comparison With the standard compound physostiomine.